The Influence of Product Presentation in Online Fashion Retail on Purchase Decisions with Shopping Lifestyle as a Moderating Variable - Zahratul Musyarrofah (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to analyze the influence of product presentation in online fashion retail on purchase decisions, with shopping lifestyle as a moderating variable. Data were collected from 205 respondents through a survey and analyzed using Structural Equation Modeling (SEM) version 26 to examine both direct and moderating effects. The analysis results show that coordinated product presentation (C.R. = 7.695; P = 0.000) and separated product presentation (C.R. = 5.716; P = 0.000) positively and significantly effect on purchase decisions. Additionally, the shopping lifestyle was found to moderate the effect of coordinated product presentation on purchase decisions (C.R. = 4.697; P = 0.000) and the impact of separated product presentation on purchase decisions (C.R. = 5.591; P = 0.000), where a more active shopping lifestyle strengthens the relationship between product presentation and purchase decision.